Effect of Waste Marble Powder and Fly Ash on the Rheological Characteristics of Cement Based Grout - Muhammet Çınar; Mehmet Karpuzcu; Hanifi Çanakcı (Salehan Institute of Higher Education, 2019)
This paper shows the results of an experimental study conducted to research the impact of waste marble powder (WMP) and fly ash (FA) on the fluidity (marsh cone flow time (MCFT), mini-slump diameter and plate cohesion meter (PCM)) and the rheological properties (viscosity and yield stress) of cement based grout (CBG) mixtures. The experiments were applied with the CBG mix including 1.00 water-binder (w/b) ratios and combined use of WMP (5-25%), FA (5-25%) and WMP+FA (10-30% + constant 25%). Test results illustrated that the rheological properties of the CBGs importantly have been improved by the addition of WMP, FA and WMP+FA to grout mix at w/b=1 ratio. Strongly shear thickening behaviour was got from the CBG mixtures the all WMP, FA and WMP+FA content. The increase in the percentage of WMP (5-25%) amount reduced the mini-slump flow diameter. Moreover, the increment in the percentage of FA (5-25%) amount increments the mini slum flow. According to the control sample, the increment in the percentage of WMP (10-25%) amount increased the mini-slump flow diameter for constant FA (25%) content. Also, the increase in WMP amount in the CBG mix, there is no effect on MCFT. Also, MCFT decreased with the increase of FA amount. Especially, FA increased the fluidity of CBG, when the WMP showed negative effect in increase the MCFT in WMP+FA content.